Revisão, filogenia e biogeografia de Eugenia Sect. Phyllocalyx (Myrtaceae) - Mariana de Oliveira Bünger (2015)
This work comes to supply knowledge gaps about one of the most riches genus of Flowering Plants in Brazil. The first chapter recalls the evolutionary history of a clade of Eugenia using tools like molecular phylogeny and morphological reconstruction. Identifies thus Eugenia sect. Phyllocalyx as paraphyletic and suggests that the bracteoles present in mature fruits and deltoid bracteoles format are synapomorphies of this section. Niche modeling analysis were provides to indentify stable areas for the clade. The southern / southeastern Atlantic Forest was highlighted as stable area of occurrence of these species and represents a novelty in relation to climatic refuges Quaternary. The second chapter is a taxonomic split of phylogenetic analysis and circumscribes and prepares a synopsis of the new section. The new section has six species distributed in the Atlantic Forest and Amazon. It also presented an identification key for the species. The third chapter elaborates the taxonomic revision for Eugenia sect. Phyllocalyx and revisits the categories of threat of extinction for each species. The species are described, taxonomic notes and geographical data are presented as well as an identification key for the sixteen species of the section. Finally, the last chapters (four, five, six and seven) show new nomenclatural within Eugenia sect. Phyllocalyx as synonymous, lectotiypes and description of four new species.